ACCESS CONTROLLR FOR INDIAN ARMY GATE USING ARDUINO (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The primary purpose of project is it to offer security to army gate, for most of commercial & residential area is we can use this system. Gate control system is the essential access control system is helping security teams actively defend & monitor the entry points, detect would be objects & grant the access to authorized person. The benefits of access control security and we can use this project residence & commercial area.